Frontoethmoid and Intraorbital Meningoencephalocele: A Case Report - Sharma, Umesh Kumar; Thapaliya, Suraj; Shrestha, Manmohan Bir; Nepal, Prajwal; Limbu, Jayanti; Thapa, Dinesh Kumar (Medical Journal of Eastern Nepal, 2023)
A 12 month old infant with progressive left sided proptosis was evaluated by ultrasound and computed tomography (CT). A diagnosis of congenital frontoethmoid and left intraorbital meningocele was made, which is very rare.